MANIFESTATION OF THINKING AND DECISION MAKING STYLES IN INTELLECTUAL ACTIVITY (ON THE EXAMPLE OF CHESS) - Manukyan, M. A. (Modern Psychology, 2019)
The article is devoted to the study of the relationship of features of decisionmaking styles, thinking and personality traits in the intellectual activity of a chess player. For this purpose, a study was conducted in which chess players and a control group (people with technical education) took part. Psychological tests adapted in Armenian were used. There are statistically significant connections between personality traits, individual decision-making styles, and thinking styles.
Keywords: Thinking styles, intellectual activity, individual decision-making style, personality traits, chess players